Pengaruh Kepuasan Terhadap Loyalitas Konsumen Menggunakan Lapangan Graha Futsal Center di Kota Pontianak - Untung Pribadi; Edy Suryadi; Neni Triana Maswardi (Jurnal Produktivitas: Jurnal Fakultas Ekonomi Universitas Muhammadiyah Pontianak, 2018)
This study aims to determine the effect of satisfaction on consumer loyalty using the Pontianak Graha Futsal Center field. This study uses descriptive method with data collection techniques consisting of observation, interviews, and questionnaires. The population in this study were all consumers who used the Pontianak Graha Futsal Center field service.  The sample used in this study was 100 people with purposive sampling technique, namely sample collection techniques with the following considerations: had used Pontianak Graha Futsal Center field services at least 2 (two) times, and consumers made payments on their own behalf. The validity of X (satisfaction) and Y (consumer loyalty) test results are declared valid. Based on the reliability test shows the value of Cronbach’s alpha on satisfaction variable (X) is 0.813 greater than 0.60. Therefore, the reliability test on satisfaction variable is reliable, while the reliability test results of the consumer loyalty variable (Y) shows the value of Cronbach’s alpha of 0.793 greater than 0.60. Therefore, reliability testing on consumer loyalty (Y) is also reliable. For the regression equation of this study, which can be arranged in the regression equation Ŷ = 1.836 + 0.693X. the correlation coefficient (R) obtained is 0.462. the coefficient of determination (R2) or R Square is 0.206.